2015
DOI: 10.1161/jaha.115.002137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineralocorticoid Receptor Antagonists on Cardiac Structure and Function in Patients With Diastolic Dysfunction and Heart Failure With Preserved Ejection Fraction: A Meta‐Analysis and Systematic Review

Abstract: BackgroundThere has been an increasing interest in use of mineralocorticoid receptor antagonists (MRAs) in patients with heart failure with preserved ejection fraction (HFPEF). However, a comprehensive evaluation of MRA effects on left ventricular (LV) structure and function in these patients is lacking. In this meta‐analysis, we evaluated the effects of MRAs on LV structure and function among patients with diastolic dysfunction or HFPEF.Methods & ResultsRandomized, controlled clinical trials evaluating the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…Previous clinical studies demonstrate that spironolactone reduces the circulating serum levels of PICP in asymptomatic patients with LVDD . This study reports for the first time that spironolactone treatment is associated with a reduction in serum PICP in patients with HFpEF.…”
Section: Discussionsupporting
confidence: 52%
“…Previous clinical studies demonstrate that spironolactone reduces the circulating serum levels of PICP in asymptomatic patients with LVDD . This study reports for the first time that spironolactone treatment is associated with a reduction in serum PICP in patients with HFpEF.…”
Section: Discussionsupporting
confidence: 52%
“…Despite potential LS improvement in patients randomized to spironolactone, this treatment was not associated with significant differences in measures of LV mass or dimensions in the 239 patients with echocardiographic follow‐up at 12–18 months after randomization . A meta‐analysis of MRA trials in HFpEF found a potential association with diastolic improvement in patients treated with MRAs as assessed by E/E′, deceleration time and E/A ratio, and, in addition, cardiac collagen markers were significantly reduced with MRA therapy …”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 98%
“…De forma global, revisando distintos metaanálisis, se podría decir que los AA no demuestran reducción de mortalidad, aunque sí reducen hospitaliza-ciones, aportan mejoría en calidad de vida y mejoran parámetros de disfunción diastólica (38,39) .…”
Section: Antialdosterónicos (Aa)unclassified